Computer-based Malay stuttering assessment system [electronic resource] - 237526 Ooi, Chia Ai (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2007